Measuring the Level of Written Expression for Sixth Graders - Aryan Hussein Sulaiman Dzaiy; Hassan Ali Abd Jawad (Zanco Journal of Human Sciences, 2025)
The main objective of the research was to know the "level of written writing among sixth grade primary school students", and the researchers selected a sample of (240) male and female students from sixth grade primary school to achieve the goal of the study. The researchers used the correct expressive performance criteria the expressive performance exam was used on the research sample in order to gauge the performance level of sixth grade primary school pupils, and it was discovered that there was a statistically significant difference (at a significance level of 0.05) between the theoretical average of the correction criterion and the average writing scores of sixth grade primary school students after the students' responses were corrected and the data was statistically processed. With the findings and conclusions in mind, the researchers suggested the following: Adding two lessons per week, one for oral expression and one for written expression, to the number of lessons allocated for teaching expression. Focus on (written expression) starting from the primary stage by following an integrated curriculum in the branches of the subject (Arabic language). Allowing students to choose expressive lesson topics that are personal to them and compatible with their interests.